The genus Liocanthydrus in Venezuela (Coleoptera: Noteridae) with description of two new species - García R., Mauricio M. (2018)
The genus Liocanthydrus contains rare species, as they are not abundant and lack records to indicate their distribution. The genus has undergone several taxonomic changes, from its first status as a subgenus to the current genus status. Two species of Liocanthydrus (Noteridae: Noterini) are described. Liocanthydrus ramosae sp. nov. and L. distintus sp. nov., both collected manually, in two freshwater microhabitats, from the Aguaro and Orinoco rivers, in the plains of Venezuela. Habits of the present species in Venezuela and the genitals structures of the two species described are included. A key is constructed to identify the species Liocanthydrus.